Modeling and extensive analysis of the energy and economics of cooling, heat, and power trigeneration (CCHP) from textile wastewater for industrial low-grade heat recovery - Dehghani, Mohammad Javad; Kyoo Yoo, Chang (Energy conversion and management, 2020)
[Display omitted] •Trigeneration of cooling, heat, and power by yielded biofuel from the textile wastewater.•An integrated system modeling based on thermodynamic and economic viewpoints.•Employing two-stage thermophilic and mesophilic processes in biofuel production.•Proposing a novel refrigeration cycle for cooling generation from low-grade waste heat.•Harvesting waste heat to use in biofuel generation and bottoming cycle, simultaneously. The wastewater of the textile industry has approximately 60 °C of temperature and a sufficient quantity of organic compounds for biofuel yielding. The low-grade heat recovery and biofuel extractability of the effluent are considered to be two potentials for the generation of the various energy demands such as cooling, heat, and power (CCHP). In this study, a novel cascade trigeneration system driven by a biofuel production source (BPS) from the textile wastewater is introduced and modeled energetically and economically. The BPS system consists of two separate thermophilic and mesophilic stirred tanks, which operate based on the anaerobic digestion process. The CCHP system comprises a Brayton top power cycle (BC) and three bottoming sub-systems, including the Rankine power cycle (RC), modified Kalina/vapor-compression refrigeration system (KVC34), and water heating unit (WHU). The feasibility demonstration and parametrical optimization of the proposed system were conducted from thermal, technical, and economic points of view. The results demonstrated that that textile wastewater has a transcendent potential for biofuel production. Moreover, the methane content of biofuel was enhanced by roughly 28% by dividing the AD process into two separate thermophilic and mesophilic reactors. additionally, the synchronic cooling, heating, and power efficiency of the trigeneration system was around 62%, with approximately five years of the discounted payback period.